A home-based health care programme to facilitate coping in survivors of cerebro-vascular accidents and their Caregivers in Oshana Region, Namibia - Kuugongelwa, Suama; Small, Louis (International Journal of Advanced Nursing Studies, 2016)
A cerebro-vascular accident entails the sudden death of brain cells resulting from a problem with the blood supply. The patient is consequently left with varying degrees of disability, and usually requires the assistance of a caregiver. This article describes the development of a home-based health care programme intended to facilitate optimal functioning, which formed the final phase of a qualitative study that explored and described the experiences of survivors of cerebrovascular accidents and their caregivers. The development of this programme was based on the four themes that emerged from the original study and which were conceptualised by applying Dickoff, James and Wiedenbach’s (1968) practice theory. These four themes were restructured as four dynamics, namely, reframing knowledge and skills regarding self-care, modifying the daily routine, assisting with the adjustment to altered social relationships, and reframing negative emotions. The programme was implemented over four days and an evaluation was done after two months. The feedback revealed that the survivors and their caregivers had benefitted with regard to the skills and knowledge gained from the educational programme.